Identification of a Single Nucleotide Polymorphism at Hinf-1 Enzyme Restriction Site of Pit-1 Gene on Indonesian Bali Cattle Population - Jakaria Jakaria; Ronny R Noor (Faculty of Animal Science, Bogor Agricultural University, 2015)
This study aimed to determine the Pit-1|Hinf-1 gene polymorphism in Bali cattle (Bos javanicus) as Indonesian native cattle and besides Madura, Pesisir, Aceh, and Katingan cattle breeds as a comparison. DNA samples were extracted from 488 blood samples consisting of Bali (245 heads), Madura (68 heads), Aceh (25 heads), Pesisir (100 heads) and Katingan (50 heads) cattle. The diversity of the Pit-1|Hinf-1 gene wasere analyzed using PCR-RFLP. Whereas the nucleotide base mutations were identified by sequencing. Genotyping data were analyzed by calculating the allele frequency, observed heterozygosity (Ho) and expected heterozygosity (He) values as well as Hardry-Weinberg equilibrium test using POPGENE 1.31 program. Whereas, Tthe sequence data were analyzed by using MEGA6 program. The Pit-1|Hinf-1 gene fragment analysis showed that Bali, Madura, Pesisir, Aceh, and Katingan cattle had high BB genotype, resulting in B allele frequency of 0.982, 0.963, 0.925, 0.960, and 0.960, respectively. Ho and He values were 0.074-0.130 and 0.036-0.139, respectively. Hardy-Weinberg equilibrium test did not significant for all breed populations, except for Aceh cattle population (P<0.05). Mutation from guanine (G) to adenine (A) was found in Pit-1 gene fragment. Therefore, Pit-1|Hinf-1 gene fragment had low genetic diversity in Bali cattle and other breeds population.Key words: Bali cattle, Pit-1|Hinf-1 gene, polymorphism